2013
DOI: 10.5812/hepatmon.6590
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Viral DNA Among HBs Antigen Negative Healthy Blood Donors

Abstract: BackgroundPresence of occult hepatitis B infection (OBI) renders HBs antigen (HBsAg) undetectable by ELISA. Therefore it is valuable to evaluate the frequency of OBI among healthy blood donors to improve and perhaps change the strategies of blood screening to reduce the risk of HBV transmission.ObjectivesThe aim of this study was to determine the presence of HBcAb and HBV DNA among Iranian HBsAg negative healthy blood donors who donated their blood to the Tehran Blood Transfusion Center during 2011.Patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 26 publications
(25 reference statements)
1
21
0
Order By: Relevance
“…This result is in agreement with that was reported by Lebanese researchers in 2007, whom found that 5.4% of healthy blood donors with core antibody have detectable viral load (El-Zaatari, et al, 2007) as well as our results compatible with that was previously reported by Iranian researchers in 2013 whom found half of anti-HBc Abs positive samples were also positive for HBV-DNA among Iranian blood donors (Vaezjalali, et al, 2013). Also our results in line with recently published report in Malaysia, they were found that the 5.5% prevalence of occult hepatitis B among Malaysian blood donors (Hudu, et al, 2016).The high percentage in this study may be due to the small size of the study population compared with above studies.…”
Section: Discussionsupporting
confidence: 94%
“…This result is in agreement with that was reported by Lebanese researchers in 2007, whom found that 5.4% of healthy blood donors with core antibody have detectable viral load (El-Zaatari, et al, 2007) as well as our results compatible with that was previously reported by Iranian researchers in 2013 whom found half of anti-HBc Abs positive samples were also positive for HBV-DNA among Iranian blood donors (Vaezjalali, et al, 2013). Also our results in line with recently published report in Malaysia, they were found that the 5.5% prevalence of occult hepatitis B among Malaysian blood donors (Hudu, et al, 2016).The high percentage in this study may be due to the small size of the study population compared with above studies.…”
Section: Discussionsupporting
confidence: 94%
“…The gold standard for diagnosis of OBI is liver biopsy and detecting the presence of HBV DNA in hepatocytes (1)(2)(3). An alternative method for diagnosis of OBI is detecting HBV DNA in peripheral blood samples.…”
Section: Introductionmentioning
confidence: 99%
“…The intra-group percentage of nucleotide identity among blood donors with HBV subgenotypes D1, D2 and D3 was 98.05±0.7%, 99.1±0.35% and 98.9±0.45%, respectively. Phylogenetic relationships between the studied isolates of OHB obtained from blood donors from the Republic of Kazakhstan and reference sequences from the international GenBank database are presented in Figure. It is known that in most of the territory of the former USSR and in the countries of the Baltic region, HBV subgenotype D2 prevails, the subgenotypes A2 and D3 [46] are present, while for the countries of Central Asia the distribution of the HBV subgenotypes shifts towards the predominance of the subgenotype D1. Thus, the high occurrence of the subgenotype D1 corresponds to the previously obtained data on the molecular genetic characteristics of HBV in Central Asia, however, the increased incidence of HBV D2 and D3 is noteworthy.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the general data vary depending on the methods of virus definition, including the variety of commercial kits for detecting HBsAg and HBV DNA, and the reported prevalence of OHB, especially among healthy blood donors, varies. For example, the prevalence of HBsAg in the Iranian population and in blood donors is 2.6% and 0.4%, respectively, while the prevalence of OHB among blood donors was estimated to be slightly more than 4% [10,42,46]. Data on the prevalence of OHB in the population of the Republic of Kazakhstan could not be found, but it can be assumed that with such a high prevalence among blood donors, in the population, the OHB can also be widely spread.…”
Section: Resultsmentioning
confidence: 99%